Analisis Yuridis Akibat Hukum Pembatalan Akta Jual Beli Tanah Oleh Hakim Dalam Putusan No. 73/Pdt.G/2013/PN.Btl - Selma Azama Shibghatillah; Budi Santoso (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractLand as one of the important objects in human life can be made transitional, one of which is traded which must be preceded by Deed. The practice of buying and selling land in fact allows for a dispute which results in Akta Jual Beli (AJB) that can be submitted for cancellation, one of which is AJB No.032 / 2012 with Decision No. 73 / Pdt.G / 2013 / PN.Btl. The research method in this article uses the normative juridical method, which is a study of the principles of positive law written in legislation with the technique of collecting literature study data from secondary data. The research results of this article include: first, the Judge's consideration of the cancellation of AJB No. 032/2012 because Defendant I was not known to exist and did not provide the remainder of the payment and fines to the Plaintiffs so that the Defendant I had broken its promise / default. Second, the legal consequences of canceling the deed of sale and purchase of land no. 73 / Pdt.G / 2013 / PN.Btl can be seen from the consequences for the parties, that is: for the Plaintiffs to get the return of SHM No.03763, for Defendant I could not own the plot of land on which the house building SHM No.03763, and for the Defendant II submission to the Plaintiffs the documents, receipts for taking SHM No. 03763. Key words: legal consequences; cancellation; deed of sale and purchase of land; judge. AbstrakTanah sebagai salah satu objek yang penting dalam kehidupan manusia dapat dilakukan peralihan, salah satunya diperjual belikan yang harus didahului dengan Akta. Praktik jual beli tanah kenyataanya memungkinkan adanya sengketa yang mengakibatkan Akta Jual Beli (AJB) bisa diajukan pembatalan, salah satunya AJB No.032/2012 dengan Putusan No. 73/Pdt.G/2013/PN.Btl. Metode penelitian dalam artikel ini menggunakan metode yuridis normatif yaitu penelitian terhadap asas-asas hukum positif yang tertulis dalam perundang-undangan dengan teknik pengumpulan data studi kepustakaan dari data sekunder. Hasil penelitian dari artikel ini meliputi: pertama, Pertimbangan hakim atas pembatalan AJB No.032/2012 karena Tergugat I tidak diketahui keberadaannya dan tidak memberikan sisa pembayaran serta denda kepada Penggugat dengan demikian Tergugat I telah ingkar janji/wanprestasi. Kedua, Akibat hukum pembatalan akta jual beli tanah putusan No. 73/Pdt.G/2013/PN.Btl dapat dilihat dari akibat bagi para pihak, yaitu: bagi Penggugat berhak untuk mendapatkan pengembalian SHM No.03763, bagi Tergugat I tidak bisa memiliki tanah pekarangan diatasnya berdiri bangunan rumah SHM No.03763, dan bagi Tergugat II penyerahan kepada Penggugat surat-surat, kwitansi untuk pengambilan SHM No.03763. Kata kunci: akibat hukum; pembatalan; akta jual beli tanah; hakim.